Przednia niedokrwienna neuropatia nerwu wzrokowego w przebiegu olbrzymiokomórkowego zapalenia tętnic. Opis przypadku - Obuchowska, Iwona; Mariak, Zofia; Budrowski, Radosław (Klinika Oczna / Acta Ophthalmologica Polonica, 2006)
Giant cell arteritis is a systemic vasculitis that affects large- and medium sized arteries. The most common ophthalmic manifestation of this disease is anterior ischemic optic neuropathy, leading to acute, painless visual loss in one or both eyes. It is caused by ischemia of the optic nerve head, which is mainly supplied by the short posterior ciliary arteries. Early diagnosis is the key to correct management and prevention of visual loss in the second eye. The treatment of choice for arteritic ischemic optic neuropathy is high dose of systemic corticosteroids. Only such treatment may prevent blindness. The authors presented a case of a 62 years man with anterior ischemic neuropathy in one eye, which was diagnosed as arteritic form caused by giant cell arteritis. The correct diagnosis was based on typical clinical signs of ischemic changes in the optic nerve head and diagnostic criteria for giant cell arteritis, advocated by American College of Rheumatologists.